Comparing China's GDP statistics with coincident indicators - Aaron Mehrotra; Jenni Pääkkönen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
We use factor analysis to summarize information from various macroeconomic indicators, effectively producing coincident indicators for the Chinese economy. We compare the dynamics of the estimated factors with GDP, and compare our factors with other published indicators for the Chinese economy. The indicator data match the GDP dynamics well and discrepancies are very short. The periods of discrepancies seem to correspond to shocks affecting the growth process as neither autoregressive models for GDP itself nor various coincident indicators are able to forecast them satisfactorily.
URN:NBN:fi:bof-201408071948
Keywords: C38; O4; P2; 330; factor models; principal component; GDP; China